The use of iTCLab Kit as a Learning Media for Dynamic Systems and Control - Fachrezi, Ahriyad; Rahmat, Basuki; Risal, Muhammad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The Internet-Based Temperature Control Lab (iTCLab) kit is an instructional tool designed to facilitate the understanding of fundamental concepts in dynamic systems and control, particularly Proportional-Integral-Derivative (PID) controllers. The background of this study lies in the gap between students’ theoretical knowledge and its application in real-world systems, which often poses a challenge in learning Dynamic Systems and Control courses. This research aims to evaluate the effectiveness of using iTCLab in improving students’ understanding of both PID control theory and its practical applications. The study was conducted in three stages: development of learning modules, implementation, and evaluation involving 30 Informatics students. Assessment was carried out through knowledge tests (pre-test and post-test) and perception surveys. The results indicated an increase in the average score from 52.30 to 76.48 (+46.26%, p < 0.001, Cohen’s d = 1.86), along with positive evaluations in terms of theory–practice integration (4.30), ease of use (4.10), content relevance (4.40), and learning satisfaction (4.20) on a 1–5 scale. These findings suggest that iTCLab is effective in strengthening students’ conceptual understanding and technical skills. From a practical standpoint, iTCLab is suitable for integration into Semester Learning Plans (RPS) and further development to support Internet of Things (IoT)-based distance learning.